An Investigation into Pre-service Teachers' Experiences While Transitioning from Scratch Programming to Procedural Programming - Tijani, Fatimah; Callaghan, Ronel; de Villers, Rian (African journal of research in mathematics, science and technology education, 2020)
The use of Scratch programming in introducing text-based programming to novices at all levels of education has gained prominence in computer science but is still hardly known among pre-service teachers. With affordances of Scratch in learning text-based programming, we present an experience report on how we supported our first-year pre-service teachers' learning of procedural programming concepts with Scratch for the first time. The study follows an action research strategy conducted over two cycles with 58 pre-service teachers who were purposively sampled. Findings revealed that Scratch supported the learning of procedural programming by our first-year pre-service teachers to some extent. We, therefore, recommend that pre-service teachers be exposed to more exercises while focusing on challenging concepts such as algorithms, use of variables, repetition and control structures.